Single-shot grating-based phase-contrast imaging of a micrometer sample at a laser-driven x-ray backlighter source. (21st June 2021) - Akstaller, B.; Schreiner, S.; Hofmann, F.; Meyer, P.; Neumayer, P.; Schuster, M.; Wolf, A.; Zielbauer, B.; Ludwig, V.; Michel, T.; Anton, G.; Funk, S.
Abstract: A single-shot x-ray phase-contrast imaging technique with short exposure time allows to capture sharp images of fast dynamic processes despite low absorption contrast. We demonstrate the capabilities of a robust single-shot grating-based phase-contrast imaging setup at the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) at the GSI Helmholtzzentrum für Schwerionenforschung GmbH. A static test sample was imaged at 47-fold magnification using a laser-driven high-energy x-ray backlighter source. The retrieved transmission and phase-contrast images yield reproducible results. The reconstructed differential phase-images are quantitatively explained. In addition to the phase-images, propagation signatures are found in the data and used for result verification. The obtained results demonstrate the capabilities of the grating setup which can be used to image microscopic dynamic processes in high-energy density plasma experiments at PHELIX or similar high-power laser facilities.